Genetic diversity of the semi-feral Marismeño horse breed assessed with microsatellites - Gómez, M. P.; Landi, V.; Martínez, A. M.; Carpio, M. G.; Baena, S. N.; Bermejo, J. V. D.; Oom, M. M.; Luís, C.; Ouragh, L.; Vega-Pla, J. L. (Italian Journal of Animal Science, 2017)
Marismeño horses originated from primitive horses living around the marshes of the Guadalquivir River in Southern Spain. Throughout their evolution, they have experienced crosses with other breeds, first with horses from North Africa and thereafter with other horses. However, they have not lost their ability to adapt to the demanding marsh environment. Recently, a studbook of the breed was established, and the Breeders Association started a conservation programme. To study the relationship of the Marismeño with other breeds, a microsatellite analysis was developed, which included other ancient Southern Iberian horse populations, such as the Sorraia and Retuertas breeds. Candidates of recent crossbreeding with Marismeño horses, such as the Hispano-Arabian and the Spanish Purebred, were studied, and the Thoroughbred and the Arabian breed were used as international references. The results indicated that the Marismeño horse population maintains a great genetic diversity. Despite recent crossbreeding, the fixation index and the Hardy-Weinberg equilibrium analysis disclosed a certain homogeneity degree. A dendrogram was built using the obtained genetic distances, and clustering was performed with the software STRUCTURE, and the results reflected the genetic differentiation of the Marismeño horse from the other autochthonous Iberian breeds, although the Marismeño population has maintained a tight relationship with the Spanish Purebred. Remarkably, some relatedness between the Marismeño and the Barb horse breeds could be observed and was most likely derived from an ancient gene flow between the horses of the Iberian Peninsula and North Africa.